1988
DOI: 10.1002/1097-0142(19881101)62:9<2051::aid-cncr2820620930>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of primary hepatocellular carcinoma in Taiwan

Abstract: A case-control study was carried out to explore possible risk factors of primary hepatocellular carcinoma (PHC) in Taiwan. One hundred thirty-one PHC patients and 207 hospital control patients were interviewed and blood samples were collected for blood type and hepatitis B virus (HBV) infection marker tests. Eighty-three percent of the PHC patients were found to be hepatitis B surface antigen (HBsAg) positive as compared with 21.0% of the control patients with an odds ratio (OR) of 21.5. Hepatitis B e antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(52 citation statements)
references
References 19 publications
3
49
0
Order By: Relevance
“…4 HBV carriers have a 20-to 98-fold increased risk of HCC, 5,6 especially among the hepatitis B e antigen (HBeAg)-positive group. 7 A recent prospective study has further confirmed that positivity for HBeAg is associated with an increased risk of HCC. 8 To combat HBV infection in Taiwan, a mass immunization program has been launched on July 1, 1984, aiming first at the prevention of perinatal mother-to-infant, chronic HBV infection.…”
mentioning
confidence: 89%
“…4 HBV carriers have a 20-to 98-fold increased risk of HCC, 5,6 especially among the hepatitis B e antigen (HBeAg)-positive group. 7 A recent prospective study has further confirmed that positivity for HBeAg is associated with an increased risk of HCC. 8 To combat HBV infection in Taiwan, a mass immunization program has been launched on July 1, 1984, aiming first at the prevention of perinatal mother-to-infant, chronic HBV infection.…”
mentioning
confidence: 89%
“…Some authors indicated that active viral replication of HBV increases the risk of HCC in subjects with chronic HBV infection [5][6][7][8][9]. Yang et al [6] reported that the incidence of HCC was significantly higher in those who were HBsAg and HBeAg positive than in those who were HBsAg positive only.…”
Section: Hepatitis B Infectionmentioning
confidence: 99%
“…90 However, the association has also been refused on several occasions. [91][92][93] This inconsistency may be due to the difficulty of Figure 3 Distribution of HCC cases attributable to aflatoxin in different regions of the world and the distribution of HCC cases in South East Asia is 27%. 94 accurate assessment of aflatoxin exposure at the population or individual level.…”
Section: Role Of Aflatoxin B Causes Hepatocellular Carcinoma In Indiamentioning
confidence: 99%